Studying the impact of strategic leadership on the level of organizational learning in industrial enterprise a field study of a sample of major industrial establishments in the state of M'sila - boudjellal abderrahim; farouk herizi (My University, 2022)
The study aims to highlight the impact of strategic leadership on the level of organizational learning. It was conducted on a group of 07 major industrial enterprises in M’sila. the study population consisted to 274 people and our research ranom sample was limited to the 134 frames. the study concluded that there is a positive, statistically significant effect of strategic leadership on organizational learning at the significance level of 0.05
Keywords: leadership, strategic leadership, organizational learning